CONSUMER BRAND LOYALTY IN BRAND HERITAGE ATTRACTIONS: A BRAND EQUITY PERSPECTIVE - M. Munir Syam AR; Edy Purwanto; Moh. Kurdi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
This study tries to analyze the conceptual model of brand equity, brand trust, brand satisfaction, and loyalty of Indonesian consumers to brand heritage. This research examines the direct effect of brand equity on trust and satisfaction, the direct effect of trust on satisfaction and loyalty, and the direct effect of brand satisfaction on brand loyalty. This conceptual model tests 9 proposed hypotheses. The object of this research is Brand Heritage in Indonesia. The total sample used is 270 respondents taken through the purposive sampling technique. The respondent's criteria used are respondents who have used/consumed and bought heritage brands in Indonesia. The data was obtained through the distribution of online and offline questionnaires. The hypothesis testing was carried out using structural equation modeling (SEM). Hypothesis testing using path analysis. This study found that two dimensions of brand equity, namely perceived quality and brand association, affect consumer trust and satisfaction. On the other hand, brand awareness does not have a significant effect on trust and satisfaction. Meanwhile, consumer trust also influences satisfaction and loyalty. Then, consumer satisfaction on consumer loyalty.